Remote area nurses' perceptions of the enablers and barriers for delivering end-of-life care in remote Australia to Aboriginal people who choose to pass away on their traditional lands - Micheal Wood; Shakiah Forsyth; Heather Dawson (James Cook University, 2021)
Introduction: This research was undertaken to gain insight into what remote area nurses perceived were enablers and barriers to being involved in delivering care to an Aboriginal person with a terminal diagnosis passing away on their traditional lands. It is hoped that this gives remote area nurses, Aboriginal Australians and service providers a glimpse into what is happening in the remote areas of Australia. Remote area nurses often work in isolated and in extreme geographical locations. This also means that a significant proportion work alongside and with Aboriginal Australians. In addition, remote area nurses are often left to support people in the communities they work in under extreme and often under-resourced conditions. Methods: A literature review was undertaken on this subject and a four-section questionnaire was then developed based on the literature. This included demographic questions and two sections using an ordinal Likert scale. The Likert scale questions asked remote area nurses about the skills they felt they used to deal with particular situations and the capacity of the health service to deal with the situations. The fourth section comprised open-ended questions. Thematic analysis was undertaken on the open-ended questions. Categories and themes were developed, and the results discussed. The four-part questionnaire was designed to be anonymous, and it formed part of the questionnaire distributed to students enrolled with the School of Indigenous and Remote Health Alice Springs, Flinders University by email, and to not-for-profit membership organisation CRANAplus for distribution through their networks. Results: Remote area nurses felt that the barriers to supporting an Aboriginal Australian with a terminal diagnosis passing away on their traditional lands were a lack of support around the delivery of culturally appropriate end-of-life care, lack of a stable workforce, insufficient cultural knowledge and understanding, and a lack of guidance and support from family. They felt the enablers were effective communication with the family and Aboriginal elders providing advice to staff and direction on how they can support the family, willingness of staff to participate in care, and input from Aboriginal health practitioners. Conclusion: Remote area nurses perceived they lacked support and knowledge from several different areas, both from within their communities and outside of their communities. Despite the barriers, it was evident that remote area nurses can be very resourceful at enabling the processes of supporting Aboriginal people with a terminal diagnosis passing away on their traditional lands.